The role of annealing temperature on fracture of cold-sprayed copper deposits: Toward damage-tolerant additive manufacturing process - Sanrun He; Wenpeng Wan; Chunjie Huang; Wenya Li (Journal of Materials Research and Technology)
The limited ductility of cold-sprayed deposits presents a significant challenge for their industrial applications. This study demonstrates that post-annealing processes can effectively reduce interfacial defects (such as non-bonded interfaces) and alleviate the dislocation density that arises from severe work hardening. Using in-situ SEM micro-tensile testing, EBSD analysis and fractographic characterization, the mechanisms through which post-annealing conditions influence crack growth are elucidated. The as-sprayed copper deposit exhibits brittle fracture behavior with minimal plastic deformation, where pre-existing non-bonded interfaces serve as stress concentrators and sites for strain localization at crack tips. Annealing at 330 °C improves both strength and ductility, however many residual lack-of-bond defects remain as preferential crack nucleation sites, as evidenced by the intergranular fracture features in post-test micrographs. In contrast, the deposit annealed at 430 °C shows significant changes in the deformation behavior, including uniform grain size, the release of strain energy, extensive dislocation slip bands and macroscopic necking prior to fracture. These findings provide a mechanistic framework for designing cold sprayed components with tunable strength-ductility profiles, which is crucial for the applications of cold spray technology in load-bearing additive manufacturing processes, such as aerospace repairs and functionally graded structures.